2020
DOI: 10.3390/ijms21082814
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cancer Molecular Classifications: From Bulk Genomics to Single Cell Analysis

Abstract: Pancreatic cancer represents one of the most lethal disease worldwide but still orphan of a molecularly driven therapeutic approach, although many genomic and transcriptomic classifications have been proposed over the years. Clinical heterogeneity is a hallmark of this disease, as different patients show different responses to the same therapeutic regimens. However, genomic analyses revealed quite a homogeneous disease picture, with very common mutations in four genes only (KRAS, TP53, CDKN2A, and SMAD4) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 72 publications
0
26
0
Order By: Relevance
“…However, due to the complex components of tumor and tumor environment, it is challenging to detailly identify these ectopic genetic accumulations in cancer ( 11 13 ). Thanks to the application of single cell omics technologies in cancer study in recent years, increasing studies are profiling and landscaping the components of solid organ diseases including tumors and validating canonical gene markers and revealing novel targets and mutations ( 14 , 15 ). By using of the single cell RNA-seq, PDAC tumor mass is found to be highly heterogeneous and is composed of diverse malignant and stromal cell types, which is true in both human diseases and mouse models ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the complex components of tumor and tumor environment, it is challenging to detailly identify these ectopic genetic accumulations in cancer ( 11 13 ). Thanks to the application of single cell omics technologies in cancer study in recent years, increasing studies are profiling and landscaping the components of solid organ diseases including tumors and validating canonical gene markers and revealing novel targets and mutations ( 14 , 15 ). By using of the single cell RNA-seq, PDAC tumor mass is found to be highly heterogeneous and is composed of diverse malignant and stromal cell types, which is true in both human diseases and mouse models ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…These molecular classifications provided novel insights into the initiation and progression of PC from another perspective, revealing the existence of internal heterogeneity and the complexity of the tumour microenvironment. Therefore, understanding tumour heterogeneity and achieving a proper stratification of patients with cancer is still a major impediment to develop effective cancer therapy and to understand late and acquired therapy resistance [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Ohlund D. et al showed that inflammatory CAFs (iCAF) form a pro-tumoral population and facilitate invasion and metastasis, as well as immune suppression [ 34 ]. On the contrary, myofibroblasts (myCAF) are probably involved in stromal and endothelial growth factors secretion [ 35 ]. When comparing genes typically expressed in iCAF and myCAF with our microarray data, CAF-P had commonalities with iCAF and CAF-D with myCAF.…”
Section: Discussionmentioning
confidence: 99%